Removing Front Yard Oleander at Watkins' Home - Watkins, Howard::::::::: (1983)
Luisa Medina holding pickaxe with Chris Petersen cringing near base of 30 oleander trunks Two foot tall brick fence on east side of property; Volkswagen bug parked on street